A new baby oviraptorid dinosaur (Dinosauria: Theropoda) from the Upper Cretaceous Nemegt Formation of Mongolia - Lee, Sungjin (PLoS One, 2019)
Recent discoveries of new oviraptorosaurs revealed their high diversity from the Cretaceous Period in Asia and North America. Particularly, at the family level, oviraptorids are among the most diverse theropod dinosaurs in the Late Cretaceous of Mongolia and China. A new oviraptorid dinosaur Gobiraptor minutus gen. et sp. nov. from the Upper Cretaceous Nemegt Formation is described here based on a single holotype specimen that includes incomplete cranial and postcranial elements. The most prominent characters of Gobiraptor are its thickened rostrodorsal end of the mandibular symphysis and a rudimentary lingual shelf on each side of the dentary. Each lingual shelf is lined with small occlusal foramina and demarcated by a weakly developed lingual ridge. This mandibular morphology of Gobiraptor is unique among oviraptorids and likely to be linked to a specialized diet that probably included hard materials, such as seeds or bivalves. The osteohistology of the femur of the holotype specimen indicates that the individual was fairly young at the time of its death. Phylogenetic analysis recovers Gobiraptor as a derived oviraptorid close to three taxa from the Ganzhou region in southern China, but rather distantly related to other Nemegt oviraptorids which, as the results of recent studies, are also not closely related to each other. Gobiraptor increases diversity of oviraptorids in the Nemegt Formation and its presence confirms the successful adaptation of oviraptorids to a mesic environment.